Identification of Candidate Allosteric Modulators of the M1 Muscarinic Acetylcholine Receptor Which May Improve Vagus Nerve Stimulation in Chronic Tinnitus - Bojić, Tijana; Perović, Vladimir R.; Senćanski, Milan; Glišić, Sanja (Frontiers in Neuroscience, 2017)
Chronic tinnitus is characterized by neuroplastic changes of auditory cortex. Promising method for therapy of chronic tinnitus is vagus nerve stimulation (VNS) combined with auditory stimulation. The principle of VNS is reversal of pathological neuroplastic changes of auditory cortex towards physiological neural activity and synchronicity. VNS mechanism of action in chronic tinnitus patients is prevailingly through the muscarinic neuromodulation of auditory cortex by the activation of nc. basalis Meynerti. The aim of this study is to propose the potential pharmaceutics which may improve neuromodulatory effects of VNS. The working hypothesis is that M1 receptors have dominant role in the neural plasticity of auditory cortex. Our idea is that allosteric agonists of muscarinic receptor type 1 (M1) receptors could improve specificity and selectivity of neuromodulatory effect of VNS on auditory cortex of chronic tinnitus patients even in the circumstances of lower acetylcholine brain concentration. This intervention would also reinforce the re-learning process of tinnitus (sub)networks by acting on cholinergic memory and learning mechanisms. We performed in silico screening of drug space using EIIP/AQVN filter and selected 50 drugs as candidates for allosteric modulators of muscarinic receptors. Further filtering of these compounds by means of 3D QSAR and docking revealed 3 approved drugs –bromazepam, estazolam and flumazenil as the most promising candidates for combined chronic tinnitus therapy. These drugs should be further evaluated by biological tests and clinical trials.